Comparison of Vibrio cholerae Pathogenicity Islands in Sixth and Seventh Pandemic Strains - Karaolis, David K. R. (American Society for Microbiology, 2001)
Epidemic Vibrio cholerae strains possess a large cluster of essential virulence genes on the chromosome called the Vibrio pathogenicity island (VPI). The VPI contains the tcp gene cluster encoding the type IV pilus toxin-coregulated pilus colonization factor which can act as the cholera toxin bacteriophage (CTXΦ) receptor. The VPI also contains genes that regulate virulence factor expression. We have fully sequenced and compared the VPI of the seventh-pandemic (El Tor biotype) strain N16961 and the sixth-pandemic (classical biotype) strain 395 and found that the N16961 VPI is 41,272 bp and encodes 29 predicted proteins, whereas the 395 VPI is 41,290 bp. In addition to various nucleotide and amino acid polymorphisms, there were several proteins whose predicted size differed greatly between the strains as a result of frameshift mutations. We hypothesize that these VPI sequence differences provide preliminary evidence to help explain the differences in virulence factor expression between epidemic strains (i.e., the biotypes) of V. cholerae.